2020
DOI: 10.1161/circulationaha.119.043042
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Is Associated With Variability in Ventricular Repolarization

Abstract: Background: People living with human immunodeficiency virus (HIV+) have greater risk for sudden arrhythmic death than HIV-uninfected (HIV–) individuals. HIV-associated abnormal cardiac repolarization may contribute to this risk. We investigated whether HIV serostatus is associated with ventricular repolarization lability by using the QT variability index (QTVI), defined as a log measure of QT-interval variance indexed to heart rate variance. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 48 publications
0
26
0
1
Order By: Relevance
“…These observations have clear implications for further utility and research of QTVi. Many studies have repeatedly shown the risk-prediction capability of QTVi [ 32 , 33 , 34 , 35 , 36 ]. Nevertheless, both increased heart rate [ 37 , 38 ] and decreased heart rate variability [ 39 , 40 ] are well recognised strong risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…These observations have clear implications for further utility and research of QTVi. Many studies have repeatedly shown the risk-prediction capability of QTVi [ 32 , 33 , 34 , 35 , 36 ]. Nevertheless, both increased heart rate [ 37 , 38 ] and decreased heart rate variability [ 39 , 40 ] are well recognised strong risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an HIV transgenic mice model, a significant reduction in outward K+ currents was noted along with significantly prolonged QT interval compared to the wildtype uninfected control mice in the absence of any drug therapy 17 . Heravi et al demonstrated in a cohort of 589 HIV‐infected individuals and 534 uninfected controls that HIV‐infected individuals had a higher QT interval variability, which is a marker of repolarization lability and has been found in other cohort studies to be predictive of SCD and ventricular arrhythmias 18‐20 …”
Section: Qt Prolongation/risk Of Torsades De Pointesmentioning
confidence: 93%
“…Since HIV-infection is now a chronic disease, several comorbidities like atherosclerosis and cardiovascular disease all related to aging have become common within the population of people with HIV (Gebo et al, 2010;Clifford and Ances, 2013;Fields et al, 2013;Buggey et al, 2019;Ciccarelli et al, 2019). It is known that HIV-infected individuals have 1.5-2 times higher risk of cardiovascular disease (CVD) due to several factors like chronic inflammation, dyslipidemia, lipid abnormalities like low high-density lipoproteins (HDL), increased triglycerides, and prolonged use of ART (Wang et al, 2015;Zungsontiporn et al, 2016;Prevedel et al, 2017;Ciccarelli et al, 2019;Estrada et al, 2019;Heravi et al, 2019;Palma Reis, 2019). HIV-associated CVD is characterized by extensive loss of cardiomyocytes, increase in fibrous tissues and significant infiltration of immune cells to the heart (Prevedel et al, 2017).…”
Section: Mechanism Of Tat-mediated Cardiovascular Diseasementioning
confidence: 99%
“…A study of a multicenter AIDS cohort study (MACS) showed that there was a significant reduction in LDL and HDL from HIV-infected individuals. Commencement of ART in these individuals led to a significant increase in total cholesterol and LDL to preinfection levels while HDL remained low (Heravi et al, 2019). Interestingly, the strategies for management of antiretroviral therapy (SMART) study that examined the effect of continuous HIV-replication on CVD events showed that continuous HIV replication in individuals that discontinued therapy increased the risk of CVD compared to individuals that adhered to their therapy, clearly showing the effect of HIV replication on CVD (Siwamogsatham et al, 2019).…”
Section: Mechanism Of Tat-mediated Cardiovascular Diseasementioning
confidence: 99%